Community preferred drug delivery approaches for pilot roll-out of a potential novel paediatric schistosomiasis treatment option in two endemic counties of Kenya: A mixed methods study. - Janet Masaku; John M Gachohi; Alice Sinkeet; Mary Maghanga; Florence Wakesho; Wyckliff Omondi; Nora Monnier; Peter Steinmann; Lisa Sophie Reigl; Isabelle L Lange; Andrea S Winkler; Sammy M Njenga; et al. (Public Library of Science (PLoS), 2024)
Treating preschool age children (PSAC) for schistosomiasis has remained a challenge due to lack of a pediatric formulation. In response to this unmet need, the Paediatric Praziquantel Consortium has developed a potential novel paediatric treatment option. In advance to its roll-out to follow regulatory response, we conducted a social science study to gather information on preferred drug delivery approaches to inform implementation. A cross-sectional study was conducted in eight villages in two purposively selected Kenyan counties. A questionnaire was administered on 690 parents/guardians of PSAC at household level. Preferred drug delivery approaches were analyzed using frequencies and proportions. We conducted key informant interviews with 17 opinion leaders and 28 healthcare workers, and 12 focus group discussions with parents/guardians of PSAC and 7 with community health volunteers (CHVs). Thematic analysis was performed on the qualitative data. Majority of the 690 respondents were women 594 (86.1%) with a mean age of 34.1 (SD = 11.3, min-max = 18-86). Community-based mass drug administration (cMDA) was the most preferred drug delivery method by 598 participants (86.7%), followed by health facility/fixed points by 398 participants (57.7%). Similarly, in the qualitative data participants indicated they prefer cMDA since the CHVs who would distribute the medication are familiar with households with PSAC and are trusted to explain the drug effects. Health facilities/fixed points were the second most preferred drug delivery approach, but some health workers we interviewed expressed concern about potential understaffing and overcrowding of facilities. Appropriate timing of the drug distribution, not to interfere with farming activities, was considered critical, irrespective of the approach used. All profiles of study participants preferred cMDA over the other delivery approaches due to the convenience of receiving drugs at home and providing explanations about the new drug. For positive outcomes, adequate planning, proper timings and community involvement are highly recommended.